A Validation of England's Nineteenth Century Tithe Files, Using GIS as a Primary Tool. Issue 1 (October 2019) - Little, Malcolm; Peplow, Stephen
Abstract : The tithe files contain a large amount of agricultural production data, but have not been much used for econometric analysis. The data is the result of averaging and estimating, thus some doubt has been cast on its accuracy. This article shows that for eight counties in the southwest of England, some data from the tithe files is reasonably reliable and was recorded in a consistent manner. The article demonstrates how tithe files and other data can be geocoded with spatial information so that an analysis using Geographical Information Systems (GIS) may be performed. Three tests are carried out, showing that pastoral rents followed a 'distance decay' model; that reported arable yields were consistent with exogenous variables; and that arable rents were set with economic variables in mind.